Globalization of the world economy and analysis of its consequences - Klymova, Svitlana Olegivna (My University, 2022)
The process of globalization today is inevitable and affects all aspects of people's social life. The main impetus for the emergence and spread of the globalization process was the social and international division of labor. So, we are witnessing a rapid increase in the interconnection and interdependence between countries.
Keywords: globalization; positive and negative consequences of globalization; transnational corporations; anti-globalization movement; economies of scale; transfer price